Hydrothermal gasification of sewage sludge and model compounds for renewable hydrogen recovery: A review - He, Chao (2016)
Sewage sludge is bio-solid with high moisture content generated from wastewater treatment plants. Due to the avoidance of energy-intensive dewatering, hydrothermal conversion of sewage sludge becomes a promising technology to simultaneously achieve energy recovery and solid waste management. In order to obtain an entire understanding of applicability of hydrothermal gasification for hydrogen rich gas production from sewage sludge, this review article discussed hydrothermal conversion and gasification processes in terms of fundamental principles, operating conditions, partial oxidative gasification, and detrimental effects of intermediates. Furthermore, since organic compounds in sewage sludge are mainly composed of carbohydrates, proteins, lipids, and lignin, this article comprehensively reviewed hydrogen production from these biomass model compounds and their hydrolysis products under sub- and supercritical water. Additionally, introduction of alkali salts and heterogeneous catalysts to enhance hydrogen yield under mild temperatures and pressures in hydrothermal gasification process was also discussed. Based on bench and pilot scale studies, supercritical water gasification of sewage sludge for hydrogen production is feasible in terms of technical and economic evaluation. Given issues concerning corrosion, plugging and high operating cost, a combined supercritical water gasification and catalytic hydrothermal gasification concept is proposed as a practical strategy to directly harness hydrogen from sewage sludge in future applications.